Popkulturowa edukacja muzyczna po pandemii – nowe perspektywy - Michalak, Marcin (Studia Edukacyjne, 2024)
The aim of this article is to present the evolution, emerging trends, and contemporary challenges in the field of popular music education (PME), particularly in the context of changes prompted by the COVID-19 pandemic. The publication adopts a review-based approach. Recent research, publications, and initiatives highlight profound shifts within PME, notably the increasing emphasis on creativity, diversity, and inclusivity, as well as the expanding role of digitalization and, more recently, the integration of artificial intelligence. These transformations remain largely absent in Polish music education. However, a favorable environment for popular music education is emerging due to the growing convergence of music education and socio-cultural animation.